BIROKRASI BARU UNTUK NEW NORMAL: TINJAUAN MODEL PERUBAHAN BIROKRASI DALAM PELAYANAN PUBLIK DI ERA COVID-19 - Taufik Taufik; Hardi Warsono (Dialogue : Jurnal Ilmu Administrasi Publik, 2020)
The pandemic Covid-19 that struck Indonesia has given a new order in bureaucracy and changes in work patterns. This kind of condition is faced with bureaucracy to make changes to new normal. This study uses qualitative descriptive methods, with the type of literature research. The results of this study found that there were two dimensions of bureaucracy change, which is the change dimensions of bureaucratic institutions and changes in work system dimensions. In the dimension of bureaucratic institution change occurs over normal disruption in this case Covid-19 requires organizations to make changes to new normal. Where the bureaucracy in organizing public services prioritizes health protocols.  While in the dimension of work system there are two options, namely working at home and still working in the office but still pay attention to the health protocol. The condition of Covid-19 has resulted in many innovations in public services based on electronics, so it is necessary to strengthen quality and innovative HR ASN, as well as infrastructure development support. The implications of this research that the success of bureaucracy change are heavily influenced by leadership factors. Leaders who have personality, visionaries, and the sense of power are able to deal with changes in the organization.